2015
DOI: 10.1016/j.jphys.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Supervised exercise reduces cancer-related fatigue: a systematic review

Abstract: PROSPERO CRD42013005803.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 49 publications
(72 reference statements)
3
104
1
7
Order By: Relevance
“…The positive effects generated by the meta-analyses for a range of inflammatory mediators justify investigation into the mechanisms underlying these effects so that exercise training exercise can be more precisely prescribed to optimize the prognosis of people with breast cancer. In the interim, exercise training can be encouraged in people during or after breast cancer treatment: because of its known benefits on the problems that cancer induces in physical fitness, function, fatigue, depression, and quality of life (23,24,32,34,35,(48)(49)(50)(51); because of the favorable trends observed in survival with exercise training (38,39); and now also, given the results of this review, because of its positive effects on inflammatory mediators in the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects generated by the meta-analyses for a range of inflammatory mediators justify investigation into the mechanisms underlying these effects so that exercise training exercise can be more precisely prescribed to optimize the prognosis of people with breast cancer. In the interim, exercise training can be encouraged in people during or after breast cancer treatment: because of its known benefits on the problems that cancer induces in physical fitness, function, fatigue, depression, and quality of life (23,24,32,34,35,(48)(49)(50)(51); because of the favorable trends observed in survival with exercise training (38,39); and now also, given the results of this review, because of its positive effects on inflammatory mediators in the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Aunque los efectos del ejercicio de resistencia no han sido descritos claramente por la ASCO 47 , existen pruebas de los posibles efectos en la percepción de fatiga en personas con cán-cer de mama 48,49 . Sin embargo, para entender los posibles mecanismos del beneficio de este tipo de entrenamiento, se requiere de información adicional sobre los efectos de la quimioterapia y la radiación en las células satélite musculares o progenitoras que se activan en respuesta al entrenamiento de fuerza.…”
Section: Figuraunclassified
“…6 However, these recommendations may not recognise the specific health needs of cancer survivors. Recent reviews have reported a low number of adverse events in relation to exercise trials, 6,7,[18][19][20] suggesting that exercise is generally safe for cancer survivors. However, in these reviews, there has been variable reporting of the dose of prescribed exercise.…”
Section: Introductionmentioning
confidence: 99%
“…36 Fatigue is a complex multi-dimensional construct related to reduced physical function and reduced health-related quality of life. 27,37 Recent reviews have concluded that exercise reduces cancerrelated fatigue, 19,[38][39][40] but the optimal dose to achieve this has not been established. It has been suggested that patients undergoing treatment may need to exercise at a lower intensity or for a shorter duration than those who have completed primary treatment.…”
Section: Introductionmentioning
confidence: 99%